Reactive dissolution of plagioclase in a basaltic melt: A chronometer for pre-eruptive volcanic processes - M. Masotta; F. Colle; S. Costa; P. Landi (Earth and Planetary Science Letters, 2025)

Effect of undercooling on clinopyroxene crystallization in a high K basalt: Implications for magma dynamics at Stromboli volcano - F. Colle; M. Masotta; S. Costa; S. Mollo; P. Landi; A. Pontesilli; S. Peres; L. Mancini (Lithos, 2023)

Ectoparasites of small mammals in a fragmented area of the southern Amazonia: interaction networks and correlations with seasonality and host sex - Ravena F. B. de Mendonça; Ana C. Colle; Leodil C. Freitas; Thiago F. Martins; Maurício C. Horta; Glauber M. B. Oliveira; Richard C. Pacheco; Lúcia A. F. Mateus; Rogério V. Rossi (Experimental and Applied Acarology, 2020)

A Review of Historical and Future Changes of Extratropical Cyclones and Associated Impacts Along the US East Coast - Brian A. Colle; James F. Booth; Edmund K. M. Chang (Current Climate Change Reports, 2015)

Specific magnetic isolation for direct detection of HPV16 - S. Peeters; T. Stakenborg; F. Colle; C. X. Liu; L. Lagae; M. Ranst (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Niche segregation and genetic structure of Campylobacter jejuni populations from wild and agricultural host species - SAMUEL K. SHEPPARD; FRANCES M. COLLES; NOEL D. McCARTHY; NORVAL J. C. STRACHAN; IAIN D. OGDEN; KEN J. FORBES; JOHN F. DALLAS; MARTIN C. J. MAIDEN (Molecular Ecology, 2011)
Bacterial populations can display high levels of genetic structuring but the forces that influence this are incompletely understood. Here, by combining modelling approaches with multilocus sequence data for the zoonotic pathogen Campylobacter, we investigated how ecological factors such as niche (host) separation relate to population structure. We analysed seven housekeeping genes from published C. jejuni and C. coli isolate collections from a range of food and wild animal sources as well as abiotic environments. By reconstructing genetic structure and the patterns of ancestry, we quantified C. jejuni host association, inferred ancestral populations, investigated genetic admixture in different hosts and determined the host origin of recombinant C. jejuni alleles found in hybrid C. coli lineages. Phylogenetically distinct C. jejuni lineages were associated with phylogenetically distinct wild birds. However, in the farm environment, phylogenetically distant host animals shared several C. jejuni lineages that could not be segregated according to host origin using these analyses. Furthermore, of the introgressed C. jejuni alleles found in C. coli lineages, 73% were attributed to genotypes associated with food animals. Our results are consistent with an evolutionary scenario where distinct Campylobacter lineages are associated with different host species but the ecological factors that maintain this are different in domestic animals such that phylogenetically distant animals can harbour closely related strains.

Dynamics of Campylobacter colonization of a natural host, Sturnus vulgaris (European Starling) - F. M. Colles; N. D. McCarthy; J. C. Howe; C. L. Devereux; A. G. Gosler; M. C. J. Maiden (Environmental Microbiology, 2009)
Summary Wild European Starlings ( Sturnus vulgaris ) shed Campylobacter at high rates, suggesting that they may be a source of human and farm animal infection. A survey of Campylobacter shedding of 957 wild starlings was undertaken by culture of faecal specimens and genetic analysis of the campylobacters isolated: shedding rates were 30.6% for Campylobacter jejuni , 0.6% for C. coli and 6.3% for C. lari. Genotyping by multilocus sequence typing (MLST) and antigen sequence typing established that these bacteria were distinct from poultry or human disease isolates with the ST‐177 and ST‐682 clonal complexes possibly representing starling‐adapted genotypes. There was seasonal variation in both shedding rate and genotypic diversity, both exhibiting a maximum during the late spring/early summer. Host age also affected Campylobacter shedding, which was higher in younger birds, and turnover was rapid with no evidence of cross‐immunity among Campylobacter species or genotypes. In nestlings, C. jejuni shedding was evident from 9 days of age but siblings were not readily co‐infected. The dynamics of Campylobacter infection of starlings differed from that observed in commercial poultry and consequently there was no evidence that wild starlings represent a major source of Campylobacter infections of food animals or humans.